Calibration of RGBD camera and cone-beam CT for 3D intra-operative mixed reality visualization - Lee, Sing Chun; Fuerst, Bernhard; Fotouhi, Javad; Fischer, Marius; Osgood, Greg; Navab, Nassir (International Journal of Computer Assisted Radiology and Surgery, 2016)
Purpose: This work proposes a novel algorithm to register cone-beam computed tomography (CBCT) volumes and 3D optical (RGBD) camera views. The co-registered real-time RGBD camera and CBCT imaging enable a novel augmented reality solution for orthopedic surgeries, which allows arbitrary views using digitally reconstructed radiographs overlaid on the reconstructed patient’s surface without the need to move the C-arm. Methods: An RGBD camera is rigidly mounted on the C-arm near the detector. We introduce a calibration method based on the simultaneous reconstruction of the surface and the CBCT scan of an object. The transformation between the two coordinate spaces is recovered using Fast Point Feature Histogram descriptors and the Iterative Closest Point algorithm. Results: Several experiments are performed to assess the repeatability and the accuracy of this method. Target registration error is measured on multiple visual and radio-opaque landmarks to evaluate the accuracy of the registration. Mixed reality visualizations from arbitrary angles are also presented for simulated orthopedic surgeries. Conclusion: To the best of our knowledge, this is the first calibration method which uses only tomographic and RGBD reconstructions. This means that the method does not impose a particular shape of the phantom. We demonstrate a marker-less calibration of CBCT volumes and 3D depth cameras, achieving reasonable registration accuracy. This design requires a one-time factory calibration, is self-contained, and could be integrated into existing mobile C-arms to provide real-time augmented reality views from arbitrary angles.
CRIS-Team Scopus Importer:2023-03-08
Keywords: 3D-3D calibration; Augmented reality; C-arm; Cone-beam CT; Intra-operative imaging